2022
DOI: 10.1007/s11258-022-01248-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and altered fire regimes: impacts on plant populations, species, and ecosystems in both hemispheres

Abstract: are reshaping our planet. We place these studies in the context of broader advances, and highlight additional research directions to uncover how altered fire regimes, fires interacting with other disturbances, and pre-and post-fire demographic processes can erode resilience in a warming climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…In addition to explaining what a fire regime is and how it may be changed in each of these three distinct ecosystem types, this part presents the ideas of fire-dependent, firesensitive, and fire-independent ecosystems [4,59]. To successfully preserve biodiversity, it is necessary to understand the effects of changing fire regimes on ecosystems and people.…”
Section: Fire In Ecosystems and Societymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to explaining what a fire regime is and how it may be changed in each of these three distinct ecosystem types, this part presents the ideas of fire-dependent, firesensitive, and fire-independent ecosystems [4,59]. To successfully preserve biodiversity, it is necessary to understand the effects of changing fire regimes on ecosystems and people.…”
Section: Fire In Ecosystems and Societymentioning
confidence: 99%
“…Harvey and Enright [59] revealed that plant damage from fire is also determined by the intensity of the fire, which is affected by the rangeland's topography, the general quantity, as well as the distribution and dryness of the fuel, the weather, and soil moisture. According to Turbé et al [29], the needed intensity of the fire is less than 1000 KJ/s/m if the goal of burning the rangeland is to remove moribund material.…”
Section: Fire Effects On Vegetationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wildfires play a major role in global carbon (C) cycles and are on the rise in many regions as climate change makes vegetation more susceptible to burning (Giglio et al., 2013; Halofsky et al., 2020; Harvey & Enright, 2022). Geography, climate conditions, human disturbance, and plant community composition shape regional fire regimes (Bond, 2013).…”
Section: Introductionmentioning
confidence: 99%